1995
DOI: 10.1002/ijc.2910640113
|View full text |Cite
|
Sign up to set email alerts
|

Significance of tenascin serum level as tumor marker in primary colorectal carcinoma

Abstract: Tenascin serum levels were evaluated in 118 patients with primary colorectal carcinoma and in a control group of 51 healthy persons in a double-sided sandwich ELISA. The data were correlated with post-operative TNM-staging. Patients with colorectal carcinomas had significantly higher serum levels of tenascin than the control group. At the 95% level of specificity, sensitivity was 25%. Tumor grading obviously had no influence on the level of tenascin in serum. With increasing pT-category, tenascin levels increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
1

Year Published

1995
1995
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 19 publications
2
26
1
Order By: Relevance
“…This finding has been described by others in colorectal cancer (Sugawara et al, 1991;Riedel et al, 1992Riedel et al, , 1995Sakai et al, 1993;Hauptmann et al, 1995) and in several other tumour types (Natali and Zardi, 1989;Ibrahim et al, 1993;Moch et al, 1993;Shoji et al, 1993;Ikeda et al, 1995;Ilunga and Iriyama, 1995;Yoshida et al, 1995). Like Sugawara et al (1991), we also found two different staining patterns.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding has been described by others in colorectal cancer (Sugawara et al, 1991;Riedel et al, 1992Riedel et al, , 1995Sakai et al, 1993;Hauptmann et al, 1995) and in several other tumour types (Natali and Zardi, 1989;Ibrahim et al, 1993;Moch et al, 1993;Shoji et al, 1993;Ikeda et al, 1995;Ilunga and Iriyama, 1995;Yoshida et al, 1995). Like Sugawara et al (1991), we also found two different staining patterns.…”
Section: Discussionsupporting
confidence: 91%
“…Studies of this putative marker of the tumour matrix are also of considerable interest in colorectal cancer (Sugawara et al, 1991;Riedel et al, 1992;Sakai et al, 1993;Hauptmann et al, 1995;Riedel et al, 1995) because of the potential involvement of tenascin (or tenascin-like proteins) in cell adhesion and invasion during the metastatic process. Moreover, diagnostic and possibly therapeutic monoclonal antibodies, specific for the larger tenascin isoforms present in tumours, have been developed (Leprini et al, 1994).…”
mentioning
confidence: 99%
“…Further investigations have shown that TN also contains a site that promotes cell adhesion (Spring et al, 1989). These properties, combined with the observations that TN is involved in the migration of cells during development of embryonic tissues and the migration of keratinocytes in skin wounds (Latijnhouwers et al, 1994), leads to speculation that the overexpression of TN in tumours may be involved in the invasion process (Riedl et al, 1995;Ishihara et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Two distinct stromal staining patterns have been described in colorectal cancer [11, 28, 29], and the distribution of these patterns has been proposed as a prognostic factor, in that a diffuse stromal staining pattern may indicate an increased risk of poor outcome [28, 29]. Further, elevated preoperative serum levels of tenascin-C have been reported to reflect the total tumor burden and to correlate with metastatic disease in colorectal cancer [30]. Also, a significant relationship between tenascin mRNA expression and deep invasion and the presence of lymph node metastasis has been seen in colon carcinomas [31].…”
Section: Introductionmentioning
confidence: 99%